Isolation of HLA Bound Peptides by Immunoaffinity Capture and Identification by Mass Spectrometry. Issue 3 (26th March 2021) - Pandey, Kirti; Ramarathinam, Sri H.; Purcell, Anthony W.
Abstract: This article describes the purification of HLA‐bound peptides and their subsequent sequencing by mass spectrometry. These methods can be used for both HLA class I and class II molecules and can be adapted to different species depending on the availability of specific antibodies. Peptides can be successfully isolated from a variety of sample types, including in vitro cultured cells and primary tissues. The method involves the affinity capture of HLA‐peptide complexes and separation of peptides from HLA heavy chains, followed by tailored interrogation by mass spectrometry to take into account the non‐tryptic nature of endogenously derived HLA‐bound peptides. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of immunoaffinity column Alternate Protocol 1 : Preparation of microscale immunoaffinity column Basic Protocol 2 : Generation of cell lysate and HLA immunoaffinity purification Alternate Protocol 2 : Microscale immunoaffinity purification Basic Protocol 3 : Separation of HLA peptides by reverse‐phase high‐performance liquid chromatography (RP‐HPLC) Alternate Protocol 3 : Isolation of HLA peptides using molecular weight cutoff (MWCO) filter Basic Protocol 4 : Mass spectrometry and data analysis